Aerobic Aliphatic Hydroxylation Reactions by Copper Complexes: A Simple Clip‐and‐Cleave Concept. Issue 58 (16th September 2018) - Becker, Jonathan; Zhyhadlo, Yevheniia Y.; Butova, Ekaterina D.; Fokin, Andrey A.; Schreiner, Peter R.; Förster, Moritz; Holthausen, Max C.; Specht, Pascal; Schindler, Siegfried
Abstract: Invited for the cover of this issue are Siegfried Schindler, Peter R. Schreiner, Andrey A. Fokin, Max C. Holthausen, and co‐workers from Justus‐Liebig‐Universität Giessen, Igor Sikorsky Kiev Polytechnic Institute, and Johann Wolfgang Goethe‐Universität Frankfurt. The image depicts the clip‐and‐cleave concept for selective hydroxylation of aldehydes (adamantane 1‐carbaldehyde is shown as an example). Read the full text of the article at 10.1002/chem.201802607 . Abstract : " The results of this study demonstrate the successful transfer of biological principles to achieve the selective oxidation reaction for a particular class of organic molecules ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 15543 ff. (DOI:10.1002/chem.201802607 ).